Exercise and the Heart: Benefits, Risks and Adverse Effects of Exercise Training - Nilanka N Mannakkara; Gherardo Finocchiaro (Reviews in Cardiovascular Medicine, 2023)
Exercise has multiple health benefits and reduces cardiovascular morbidity and mortality. Regular exercise decreases the burden of cardiovascular risk factors and improves prognosis in several cardiac conditions. Despite these premises, sudden cardiac death (SCD) during sports may occur in apparently healthy athletes who perform at the highest levels. Accurate identification and prompt treatment of individuals at risk may reduce the burden of SCD. A possible cardiotoxic effect of intense exercise has been recently postulated, however this is still matter of controversy as causal relationships are often difficult to establish taking into account multiple confounders. Exercise is safe for the majority, even with cardiovascular disease. In this review, we focus on exercise and sports, discussing their benefits and risks and exercise recommendations for healthy individuals and those with cardiovascular disease.